Perceived Risk and Theory of Planned Behaviour - Imran Arshad; Irma Tayasri; Loh Chik Im; Muhammad Amsal Sahban (Jurnal Aplikasi Manajemen, Ekonomi dan Bisnis, 2021)
The purpose of this paper is to determine the investment intentions of individual investors using social psychological perspective. This research incorporates perceived risk as an additional variable (attitude) in the existing theory of planned behaviour (TPB) framework. Given the nature of this study, a quantitative approach with cross-sectional survey has been used in order to furnish some empirical evidence on investment intentions of individual investors. Where data from 548 potential investors was collected using a simple random technique and respondents were asked on their perceived risk, subjective norms and perceived behavioural control aspects with the help of well-established scales. The collected data was analysed using structural equation modelling technique with the help of SmartPLS 3.2.7. Perceived risk has a negative influence on the investment intentions of individual investors. On the other hand, subjective norm and perceived behavioural control have a positive influence on the investment intentions of individual investors. The current research is first of its kind which includes perceived risk is used as an attitudinal factor to test in the theory of planned behaviour. This study further confirmed that not only perceived risk but the subjective norm and perceived behavioural control influence the investment intentions of individual investors